Respuesta :

Answer:

The Average rate of change of function f(x)

A(x) = 3

Step-by-step explanation:

Step(i):-

Given function f(x) = x²-2

Given values x = a = -1 and  x = b =4

The Average rate of change of function f(x)

[tex]A(x) = \frac{f(b)-f(a)}{b-a}[/tex]

Given function f(x) = x²-2

                f(a) =f(-1) = (-1)²-2 = 1-2 = -1

                f(b) = f(4) = (4)²-2 = 16-2 = 14

Step(ii):-

The Average rate of change of function f(x)

[tex]A(x) = \frac{f(b)-f(a)}{b-a}[/tex]

[tex]A(x) = \frac{14-(-1)}{4-(-1)} = \frac{14+1}{4+1} = \frac{15}{5} =3[/tex]

Final answer:-

The Average rate of change of function f(x)

A(x) = 3